Imbalanced motivated behaviors according to motor sign asymmetry in drug-naïve Parkinson’s disease - Matthieu Béreau; Anna Castrioto; Mathieu Servant; Eugénie Lhommée; Maxime Desmarets; Amélie Bichon; Pierre Pélissier; Emmanuelle Schmitt; Hélène Klinger; Nadine Longato; Clélie Phillipps; Thomas Wirth; et al. (Scientific Reports, 2023)
Abstract Few studies have considered the influence of motor sign asymmetry on motivated behaviors in de novo drug-naïve Parkinson’s disease (PD). We tested whether motor sign asymmetry could be associated with different motivated behavior patterns in de novo drug-naïve PD. We performed a cross-sectional study in 128 de novo drug-naïve PD patients and used the Ardouin Scale of Behavior in Parkinson’s disease (ASBPD) to assess a set of motivated behaviors. We assessed motor asymmetry based on (i) side of motor onset and (ii) MDS-UPDRS motor score, then we compared right hemibody Parkinson’s disease to left hemibody Parkinson’s disease. According to the MDS-UPDRS motor score, patients with de novo right hemibody PD had significantly lower frequency of approach behaviors (p = 0.031), including nocturnal hyperactivity (p = 0.040), eating behavior (p = 0.040), creativity (p = 0.040), and excess of motivation (p = 0.017) than patients with de novo left hemibody PD. Patients with de novo left hemibody PD did not significantly differ from those with de novo right hemibody PD regarding avoidance behaviors including apathy, anxiety and depression. Our findings suggest that motor sign asymmetry may be associated with an imbalance between motivated behaviors in de novo drug-naïve Parkinson’s disease.